Bronchoalveolar Activation of Coagulation and Inhibition of Fibrinolysis during Ventilator-Associated Lung Injury - M. J. Schultz; R. M. Determann; A. A. N. M. Royakkers; E. K. Wolthuis; J. C. Korevaar; M. M. Levi (Critical Care Research and Practice)
Background and Objective. Bronchoalveolar coagulopathy is a characteristic feature of pulmonary inflammation. We compared bronchoalveolar and systemic levels of coagulation in patients who did and patients who did not develop ventilator-associated lung injury (VALI). Methods. Secondary analysis of a randomized controlled trial evaluating the effect of lower tidal volumes versus conventional tidal volumes in patients without acute lung injury or acute respiratory distress syndrome at the onset of mechanical ventilation. Results. Ten patients with VALI and 10 random control patients without lung injury during the course of mechanical ventilation, but all ventilated with conventional tidal volumes, were compared. Patients who developed VALI showed both bronchoalveolar activation of coagulation (increase in thrombin–antithrombin complex levels P<0.001 versus baseline) and inhibition of fibrinolysis (decline in plasminogen activator activity P<0.001 versus baseline). The later seemed to be dependent on higher levels of plasminogen activator inhibitor type 1 (P=0.001 versus baseline). Patients who developed VALI also showed elevated systemic thrombin-antithrombin complex levels and decreased systemic plasminogen activator activity levels. Conclusions. VALI is characterized by bronchoalveolar coagulopathy. Systemic and bronchoalveolar coagulopathy at the onset of mechanical ventilation may be a risk factor for developing VALI in patients ventilated with conventional tidal volumes.